Hak Anak Angkat terhadap Warisan dalam Waris Perdata dan Islam: (Studi Kasus Putusan Pengadilan Negeri Palangkaraya No. 27/Pdt.g/2019/Pn.Plk) - Nabillah; Rosnidar Sembiring; Utary Maharany Barus (CV Rewang Rencang, 2025)
Child adoption serves as an alternative for couples who have not been blessed with children; however, it raises legal issues, paticularly regarding the inheritance rights of adopted children. Under civil law, adopted children are entiled to inheritance rights equivalent to those of biological children,in contrast, islamic law does not grant adopted children direct inheritance rights;instead, they may recive inheritance through a wasiat wajibah (mandatory will). This disrepancy creates legal uncertaintly in juridical practice, as reflected in the palangkaraya Distric Court Decision No. 27/Pdt.G/2019/PN.PLK. This study employs a normative legal research method with descriptive analytical approach and Comparative legal. The findings reveal that although adopted children do not have automatic inheritance rights under either legal system, islamic law provides protection through the wasiat wajibah mechanism (up to one-third of the estate), while civil law relies on will and grants.